2019
DOI: 10.1111/ans.15166
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open transverse‐incision right hemicolectomy: a retrospective comparison study

Abstract: Background The optimal surgical approach to right colon cancer is still under debate. The aim of the present study was to compare the short‐ and long‐term outcomes of laparoscopic and transverse‐incision open approaches to right hemicolectomy for colon cancer. Methods Data on 99 adult patients with right‐side colon cancer undergoing either laparoscopic or open transverse‐incision right hemicolectomy at two different university hospitals, between January 2013 and December 2016, were retrospectively reviewed. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Even for advanced colon cancer with clinical stage II/III, better short‐term outcomes and similar overall survival in laparoscopic surgery compared with open surgery with a low conversion rate of 5.4% were demonstrated by the Japan Clinical Oncology Group (JCOG) 0404 trial 9,10 . When focusing on LRH, similar outcomes in favor of laparoscopic surgery were demonstrated by recent studies 11–16 . In 2015, Arezzo et al reported that the mortality and morbidity rate was lower in the laparoscopic group than the open group (1.2% vs 3.4%; P = .031; and 16.8% vs 24.2%; P = .007, respectively) based on their systematic review on 3049 patients 11 .…”
Section: Laparoscopic Vs Open Approachmentioning
confidence: 83%
See 1 more Smart Citation
“…Even for advanced colon cancer with clinical stage II/III, better short‐term outcomes and similar overall survival in laparoscopic surgery compared with open surgery with a low conversion rate of 5.4% were demonstrated by the Japan Clinical Oncology Group (JCOG) 0404 trial 9,10 . When focusing on LRH, similar outcomes in favor of laparoscopic surgery were demonstrated by recent studies 11–16 . In 2015, Arezzo et al reported that the mortality and morbidity rate was lower in the laparoscopic group than the open group (1.2% vs 3.4%; P = .031; and 16.8% vs 24.2%; P = .007, respectively) based on their systematic review on 3049 patients 11 .…”
Section: Laparoscopic Vs Open Approachmentioning
confidence: 83%
“…9,10 When focusing on LRH, similar outcomes in favor of laparoscopic surgery were demonstrated by recent studies. [11][12][13][14][15][16] In 2015, Arezzo et al reported that the mortality and morbidity rate was lower in the laparoscopic group than the open group (1.2% vs 3.4%; P = .031; and 16.8% vs 24.2%; P = .007, respectively) based on their systematic review on 3049 patients. 11 Moreover, Rausa et al reported in their meta-analysis a significantly higher risk of overall complication and reoperation in the open surgery group compared to the total laparoscopic surgery group.…”
Section: Aparoscopi C Vs Open Approachmentioning
confidence: 99%
“…Many studies have reported higher rates of incisional hernia in the EA group [ 25 26 ]. According to Feo et al [ 25 ], all EA specimens were extracted through the extension of the umbilicus wound, while the IA specimen extraction site varied from umbilicus, right lower quadrant trocar site, or Pfannenstiel incision. Hellan et al [ 26 ] reported the incidence of incisional hernia in IA only in patients whose specimen was not removed through a Pfannenstiel incision.…”
Section: Discussionmentioning
confidence: 99%
“…Six articles dealing with off-midline incisions were retrieved accounting for 515 patients: two were RCT [21,29] (377 patients); four were retrospective studies [35,53,88,100] (138 patients). The pooled proportion of incisional hernia in RCT was 0.02 (95% CI 0.00-0.07), I 2 52% and in retrospective studies 0.03 (95% CI 0.00-0.32) I 2 87%, without statistical differences.…”
Section: Midline and Off-midline Laparotomiesmentioning
confidence: 99%